X=-2→y=7(6)^(-2+2)+1=7(6)^0+1=7(1)+1=7+1→y=8; (x,y)=(-2,8)
x=-5→y=7(6)^(-5+2)+1=7(6)^(-3)+1=7/6^3+1=7/216+1=0.0324+1→y=1.0324→(x,y)=(-5,1.0324)
Answer: Graph 3
Answer:
y-3= -6/13 ⋅ (x-6)
Step-by-step explanation:
I hope this helps
Consider, pls, this option:
1) let start price is 'x' and the 1-t increasing is 'y';
2) after the 1-t increasing new1_price is x(y+1);
3) after the 2-d increasing new2_price is 1.25x(y+1);
4) from another side, new2_price is '2x';
5) according to five items it is possible to make up an equation: 1.25x(y+1)=2x;
1.25(y+1)=2, y=8/5 -1=3/5=0.6.
0.6 means 60%.
Answer: 60%.